Estimation the activity of Copeptin, insulin, and C-peptide from patients with polycystic ovary syndrome - Entedhar R. Sarhat; Madlen Qassm Abbas (Tikrit Journal of Pure Science)
Copeptin, the C-terminal part of the vasopressin prohormone, is secreted stoichiometrically with vasopressin that is more easily measured than Arginine vasopressin. The present study was conducted in Kirkuk Teaching Hospital in Kirkuk city during the period from June 2016 to January 2017, to determine serum copeptin concentration in women with and without polycystic ovary syndrome (PCOS) and investigate the relationship between copeptin  with insulin, and C-peptide, parameters. A total of 80 cases were enrolled in the study. All were over 18 years of age, and consisted of 40 women with POCS, and 40 healthy subjects. Blood samples were collected from all women with PCOS and healthy between 8 and 11 AM, after fasting overnight. Copeptin, insulin, and C-peptide levels in each of the cases have been measured. There was a significant increase in serum copeptin, insulin, C-peptide, and glucose levels in PCOS group when compared with healthy controls. So the copeptin assay may be a useful alternative method to direct measurement of Arginine vasopressin concentration.